2017
DOI: 10.47672/ajfsn.217
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid and Fatty Acid Composition of Ethiopian Taro

Abstract: The purpose of this study was designed to investigate the amino acid and fatty acid composition of taro leaf and corm samples. An UHPLC and GC-FID method was used for the determination of amino acids and fatty acid composition, respectively. Taro leaf was processed as a powder and pre-curd concentrates while the corm was pre-gelatinized with and without peel prior to the analysis. The amino acid and fatty acid composition (%) of the analyzed samples were quantified with their relative area comparing with respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The weaning mush prepared from these mixed flours exhibited a high energy density of 119 kcal/100 mL [99]. Temesgen et al [101] designed a pregelatinized taro flour and developed a weaning food, these authors observed that the weaning foods prepared from 25% taro flour provided better nutritional and functional compositions to meet the nutrient density of infant foods.…”
Section: Other Food Productsmentioning
confidence: 99%
“…The weaning mush prepared from these mixed flours exhibited a high energy density of 119 kcal/100 mL [99]. Temesgen et al [101] designed a pregelatinized taro flour and developed a weaning food, these authors observed that the weaning foods prepared from 25% taro flour provided better nutritional and functional compositions to meet the nutrient density of infant foods.…”
Section: Other Food Productsmentioning
confidence: 99%
“…for commonly used plant leaves in fish farming and in the human diet (Dada and Owonu, 2010;Caunii et al, 2010;Mutayoba et al, 2011;Awol, 2014;Sun et al, 2014;Temesgen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%